Transcriptome-Wide Identification of Novel UV-B- and Light Modulated Flavonol Pathway Genes Controlled by VviMYBF1 - Czemmel, Stefan; Höll, Janine; Loyola, Rodrigo; Arce-Johnson, Patricio; Alcalde, José Antonio; Matus, José Tomás; Bogs, Jochen (Frontiers in Plant Science, 2017)
Flavonols constitute a group of flavonoids with important photoprotective roles in plants. In addition, flavonol content and composition greatly influences fruit quality. We previously demonstrated that the grapevine R2R3-MYB transcription factor VviMYBF1 promotes flavonol accumulation by inducing the expression of flavonol synthase (VviFLS1/VviFLS4), a key step of the initial flavonol pathway. Despite this, gene networks underlying flavonol modification in grapevine including both structural and regulatory genes remain poorly understood. In order to identify flavonol modifying genes and transcription factors acting downstream of VviMYBF1 a microarray-based transcriptome analysis was performed on grapevine hairy roots ectopically expressing VviMYBF1 or a Green Fluorescent Protein as control. VviFLS1 was induced in VviMYBF1 transgenic roots and glycosylated flavonols accumulated significantly compared with control lines. Among the differentially expressed genes, potential flavonol-modifying enzymes with predicted rhamnosyltransferase (e.g. RhaT1) or glycosyltransferase (e.g. GT3) activities were identified. In addition, important transcription factors of the MYB and bZIP families such as the proanthocyanidin regulator VviMYBPA1 and the UV-B light responsive HY5 homologue VviHYH were significantly altered in their expression pattern by overexpression of VviMYBF1. Co-temporal expression analysis demonstrated positive correlation of VviMYBF1 with VviFLS1, VviGT3 and VviRhaT1 during berry development and in fruits ripened with different light and UV-B radiation conditions at field. These results show that VviMYBF1 overexpression led to the identification of novel genes of the flavonol pathway and that the flavonol modifying machinery can be influenced by agricultural practices to optimize flavonol composition in grapes.